Problem-Solving Strategies as The Key to Successful Student Organization Management - Haruman Putri, Risa; Nofitasari, Susi (Journal of Business Administration and Strategy, 2025)
Student organizations play an important role in developing student potential and facilitating productive student activities. However, in the course of their operations, student organizations often face various problems that can hinder their effectiveness and sustainability. Therefore, the implementation of appropriate problem-solving strategies is key in ensuring the smooth management of student organizations. This article aims to analyze the importance of problem-solving strategies in student organizations, identify the factors that influence the success of these strategies, and provide concrete examples of their implementation.